Comparative - correlational analysis of problems of neophyte teachers basis for connecting pre-service preparation and beginning years of teaching - Reyes, Flordeliza C. (2003)
The study primarily probed into the problems confronting neophyte teachers, and identified factors that could possibly explain the variance in the number of their self-reported problems. The study showed that a number of problems varies with length of teaching experience and with type of higher educational institution graduated from (government/private). The first-year teachers experienced the most number of difficulties, indicating poor preparation of new teachers for actual classroom realities. Moreover, type of undergraduate degree program (education/others) did not make a difference in the number of problems confronting neophyte teachers, suggesting that an education degree is not an infallible guarantee if teacher candidates' readiness for teaching. The participant teachers candidly revealed their self-assessed inadequacies, which teacher preparation and induction programs seemingly failed to address satisfactorily. These empirical findings have substantive implications for teacher preparation and development.
Keywords: Teacher effectiveness; Teachers